Uji Aktivitas Antibakteri Salep Hidrokarbon Ekstrak Etil Asetat Daun Jengkol (Pithecollobium labatum Benth) terhadap Staphylococcus aureus ATCC® 25923 - Ismi Rahmawati; Novia Yucca Tiara; Agnes Sri Harti (Jurnal Farmasi Indonesia, 2009)
Jengkol (Pethecollobium labatum Benth) leaf is a traditional medicine used to treat eczema, scabies, wound and ulcer, and the fruit peel is for sore. Jengkol leaf contains saponin, flavonoid, and tannin. The experiment was aimed to know the antibacterial activity of jengkol leaves ethyl acetate extract ointment against Staphylococcus aureus ATCC 25923 infection indicated by recovery time from infection on rabbit’s back with effective basic and concentration. Jengkol leaf’s ethyl acetate extract was then made into hydrocarbon basics ointments with concentrations of 10%, 20%, and 30%. The examination of the ointment consist of stability, homogenity, spreadability, adhesion capacity, protection capability, and viscosity test. The ointments were rubbed once a day on the infection area. The observation was carried out until the infection was healed which is confirmed by the disappearing of pus, drying wound, and when it was inoculated in Vogel Jhonson Agar media there was no growth of bacteria. The result of this experiment showed that the most effective ointment of jengkol leaves extract was ointment with 30% concentration. All the tests taken demonstrated that the ointment of jengkol leaves reached the standard of good ointment.